2017
DOI: 10.1177/1933719116650755
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Methylation of Imprinted Genes and Cigarette Smoking: Assessment of Their Association With the Risk of Male Infertility

Abstract: Male infertility is a complicated disease with causes generally split into 2 broad categories: genetic factors and environmental factors. The present study was designed to investigate the association between the methylation patterns of H19 and SNRPN imprinting control region (ICR) and male infertility and to assess the gene-environment interactions between environmental factors and methylation patterns. A total of 205 DNA samples from 48 oligozoospermia (OZ), 52 asthenozoospermia (AZ), 55 teratozoospermia (TZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 55 publications
1
30
0
1
Order By: Relevance
“…The authors of this study also identified that smoking is associated with changes in sperm DNA methylation patterns, specifically at CpGs located in regions related to MAPK8IP and TKR genes. A link between smoking, male fertility and methylation at imprinted loci has been highlighted in a study by Dong et al (2016). In this study, they revealed that hypomethylation of the H19 imprint control region (ICR) and hypermethylation of the SNRPN-ICR were associated with infertility and that the risk was potentiated by smoking.…”
Section: Dna Methylationmentioning
confidence: 83%
See 1 more Smart Citation
“…The authors of this study also identified that smoking is associated with changes in sperm DNA methylation patterns, specifically at CpGs located in regions related to MAPK8IP and TKR genes. A link between smoking, male fertility and methylation at imprinted loci has been highlighted in a study by Dong et al (2016). In this study, they revealed that hypomethylation of the H19 imprint control region (ICR) and hypermethylation of the SNRPN-ICR were associated with infertility and that the risk was potentiated by smoking.…”
Section: Dna Methylationmentioning
confidence: 83%
“…Given that sperm are one of the most diverse cell types (Ramon et al 2014) and that sperm have been reported to be epigenetically heterogeneous (Laurentino et al 2016), future investigations using highthroughput single cell epigenomics will be important to help determine whether aberrant infertility-related epigenetic marks are present in all spermatozoa of the ejaculate. Finally, advising couples suffering from UMI, and males in general, on known risk factors such as smoking (Dong et al 2016, Laqqan et al 2017b, obesity (Katib 2015, Craig et al 2017 and alcohol consumption (Ouko et al 2009, Lim & Song 2012 may help to reduce infertility-related epigenetic aberrancies in sperm and go some way on the long road to understanding and potentially treating male factor infertility.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in sperm histone acetylation entail similar changes in early embryos; thus, epigenetic alterations might be paternally transmitted, via SPZ, probably through changes in expression of histone acetyltransferases [ 205 ]. Chronic smoking exposure induces in sperm an elevated histone-to-protamine ratio [ 206 ], increased global acetylation of H4K8 and H4K12 [ 207 ] and abnormal methylation of imprinted genes [ 208 ]. As described in testis, Sirt1 seems to mediate most of BPA effects on male reproductive tracts [ 209 ].…”
Section: Epigenetic Mechanisms Are Sensitive To Environment and LImentioning
confidence: 99%
“…Epigenetic aberrations in imprinted genes have been associated with adverse effects on cancer [194], embryogenesis, nervous system development, and DNA repair [172,195]. Subfertile males harbored dysregulated sperm methylation profiles associated with abnormal sperm parameters [196]; specifically, hypomethylation of H19 and hypermethylation of SNRPN imprint control regions [196,197,198,199], which is exacerbated further by cigarette smoking [200]. Therefore, exposure to reproductive environmental toxins during critical windows of mammalian development can trigger irreversible and heritable epigenetic tags.…”
Section: Epigenetic Implicationsmentioning
confidence: 99%